Towards Sustainable High‐Performance Thermoplastics: Synthesis, Characterization, and Enzymatic Hydrolysis of Bisguaiacol‐Based Polyesters. Issue 15 (6th August 2018) - Curia, Silvio; Biundo, Antonino; Fischer, Isabel; Braunschmid, Verena; Gübitz, Georg M.; Stanzione, Joseph F.
Abstract: Invited for this month's cover is the group of Joseph Stanzione at Rowan University. The Cover Image is an artistic photography effort aiming to show that lignin‐derived compounds can be utilized for the preparation of sustainable, highperformance polyesters susceptible to biodegradation. The Full Paper itself is available at10.1002/cssc.201801059 . Abstract : "These novel polyesters show strong potential for a wide range of applications…" This and more about the story behind the research that inspired the Cover image is presented in the Cover Profile. Read the full text of the corresponding research at10.1002/cssc.801059 . View the Front Cover here:10.1002/cssc.201801667 .